Peran Perilaku Mencari Bantuan Profesional Jiwa Terhadap Status Kesehatan Mental Berdasarkan Tingkat Literasi Kesehatan Mental Masyarakat di Wilayah Kerja Puskesmas X Kota Sungai Penuh - Qodisha, Agusta Dyra; Hafizah, Nurul; Andriani, Annisa (Indo-MathEdu Intellectuals Journal, 2025)
The general objective of this study was to determine whether there are differences in the contribution of professional help-seeking behavior to mental health status based on the level of mental health literacy in the community's work area, Community Health Center X, Sungai Penuh City. This study was quantitative. The research approach used was correlational. Correlational analysis is a quantitative data analysis technique used to analyze two or more variables and examine the relationship between them. Based on the results of the study, it was found that professional help-seeking behavior did not significantly influence the mental health status of the community in the Community Health Center X, Sungai Penuh City, whether among high, medium, or low mental health literacy groups. This means that professional help-seeking behavior did not predict an individual's mental health status. Mental health literacy also did not strengthen either variable. Therefore, it can be concluded that neither professional help-seeking behavior nor mental health literacy are dominant factors in predicting mental health status, so other, more complex variables are needed to predict mental health status